The Relationship between Firm Size, Activity Based Costing and Performance: An Application on Moroccan Enterprises - Elhamma, Azzouz (JABM, 2012)
The Activity Based Costing (ABC) represents a new model in the management accounting. In recent decades, it has been the subject of several research papers, especially in developed countries (USA, UK, Australia, etc.). However, this type of works is still absent in developing countries like the Arab area for example. In this context, this article highlights the results of an empirical study on the relationship between firm size, ABC method and organizational performance in Morocco. The results based on a sample of 62 firms showed that 12.9% of the responding companies reported using the ABC method. The results using logistic regression indicate that the firm size influences significantly and positively the use of the ABC. Also, we found that the management accounting system based on ABC method results in a better performance for enterprises that have adopted it. Finally, we demonstrated that the large enterprises have an interest to adopt this new method of the management accounting, but the SMEs are indifferent between adopting and not adopting this method.